No Evidence of Neurogenesis in Adult Rat Sympathetic Ganglia Following Guanethidine-Induced Neuronal Loss. (January 2020) - Walters, Karen M.; Boucher, Magalie; Boucher, Germaine G.; Opsahl, Alan C.; Mouton, Peter R.; Liu, Chang-Ning; Ritenour, Casey R.; Kawabe, Thomas T.; Pryski, Hayley N.; Somps, Christopher J.
The potential for neurogenesis in the cranial (superior) cervical ganglia (SCG) of the sympathetic nervous system was evaluated. Eleven consecutive daily doses of guanethidine (100 mg/kg/d) were administered intraperitoneally to rats in order to destroy postganglionic sympathetic neurons in SCG. Following the last dose, animals were allowed to recover 1, 3, or 6 months. Right and left SCG from guanethidine-treated and age-matched, vehicle-treated control rats were harvested for histopathologic, morphometric, and stereologic evaluations. Both morphometric and stereologic evaluations confirmed neuron loss following guanethidine treatment. Morphometric analysis revealed a 50% to 60% lower number of tyrosine hydroxylase (TH)-positive neurons per unit area of SCG at both 3 and 6 months of recovery, compared to ganglia of age-matched controls, with no evidence of restoration of neuron density between 3 and 6 months. Reductions in TH-positive neurons following guanethidine treatment were corroborated by unbiased stereology of total hematoxylin and eosin-stained neuron numbers in SCG. Stereologic analyses revealed that total neuron counts were lower by 37% at 3 months of recovery when compared to age-matched vehicle controls, again with no obvious restoration between 3 and 6 months. Thus, no evidence was found that postganglionic neurons of the sympathetic nervous system in the adult rat have a neurogenic capacity.